A self-management concept for men at the community level: the 'waist' disposal challenge - Aoun, Samar; Osseiran-Moisson, Rebecca; Collins, F.; Newton, R.; Newton, M. (Sage Publications, 2009)
The Waist Disposal Challenge consisted of a health intervention at the community level to bring about a reduction in body mass index (BMI) and is delivered at three levels: educational presentations on nutrition and exercise; monthly monitoring of BMI competition; telephone lifestyle coaching with follow-ups. Twenty-three Rotary Clubs participated in Western Australia in 2007-08 (750 Rotarians). The significant to moderate decreases in BMI are an encouraging indication that such community based-projects for men at-risk of developing chronic disease may influence the way health services reorient their community programmes to suit the health psychology of middle-aged to older men.